The process of social death in patients with hip fracture - Golnar Ghane; Zahra Zare; Hooman Shahsavari; Shirin Ahmadnia; Babak Siavashi (Scientific Reports, 2024)
Abstract People with chronic disability and uncontrollable long-term complications following hip fracture have characterist.ics that may predispose them to social death. Continuous physical disability can have negative physical, psychological, and social consequences in these patients. To design care interventions for preventing and controlling social death, it is essential to identify the dimensions and characteristics of this process. Therefore, the present study aimed to explain the process of social death in hip fracture patients. In this study, which was conducted using a grounded theory approach, 20 patients were selected with maximum diversity and 9 professional and non-professional caregivers also through purposive sampling followed by theoretical sampling. Data were collected through semi-structured in-depth interviews, field notes, and observations. Data were analyzed using the approach proposed by Corbin and Strauss in stages including data analysis for concepts and their dimensions and characteristics, the context, process extraction, and integration of the categories. One core category and 16 main categories, which consisted of 55 subcategories and 212 primary concepts, were extracted. The results showed that the core process of social death in hip fracture is an intentional self-destruction for getting liberated from the conditions of the illness and the disrupted social life after the fracture, which ultimately leads to outcomes such as isolation-seeking and death ideations in these patients. The core category of liberating self-destruction reflects the close relationship between the context, process, and outcomes of social death. The process of social death is social, multidimensional, and complex. So far, no explanatory theory has been presented for this group of patients. Therefore, the results of this study can play an important role in designing helpful interventions for preventing, modifying, and changing the phenomenon of social death.